In order to solve this we need to get x by itself on one side.
We need o start by adding across the 4 so that we get:
x/3 = -7 + 4 = -3
We then need to multiply both sides by 3 to get a singular x:
x = -3 * 3 = -9
Please: Use "^" to denote exponentiation: <span>2x^2 + 8x - 12 = 0
Reduce this by div. every term by 2: </span><span>x^2 + 4x - 6 = 0
Here a=1, b=4 and c = -6. Square half of b, obtaining (4/2)^2 = 4, and add, and then subtract, this 4 to x^2 + 4x - 6:
</span> x^2 + 4x +4 - 4 - 6 = 0. Rewrite the square as (x+2)^2, obtaining new equation
(x+2)^2 = 10. Take the sqrt of both sides: x+2 = plus or minus sqrt(10).
Finally, solve for x: x = -2 plus or minus sqrt(10).
It’s c) XS, i love your pfp btw!! :)